Formulasi Busa dari Lateks Cair (Hevea brasiliensis) Asal Kabupaten Musi Rawas - Lia Aseptin Murdini; Nurkayah; Syaifudin (Konservasi Hayati, 2025)
Musi Rawas is one of the major rubber plantations (Hevea brasiliensis) in South Sumatra. However, prolonged fluctuations and the decline in natural rubber prices have contributed to reduced household income among rubber farmers, affecting their economic stability. This situation highlights the need to enhance the added value of natural rubber products as a strategy to improve farmer welfare and support the achievement of Sustainable Development Goal (SDGs) 1, which aims to alleviate poverty. One promising approach is the utilization of natural rubber latex for foam production through formulation optimization, particularly by adjusting the concentration of zinc-mercaptobenzothiazole (ZMBT), a secondary accelerator known to influence physical properties. This study aimed to evaluate the effect of ZMBT concentrations on the physical properties of natural rubber latex foam. The research was conducted from February to June 2025 at the Integrated Laboratory, Institut Teknologi Muhammadiyah Sumatera, utilizing natural rubber latex sourced from local farmers in Musi Rawas. Three ZMBT concentrations were tested, namely 0.5 phr (A), 1.0 phr (B), and 2.0 phr (C), while all other formulation ingredients were kept constant. The physical properties evaluated included Compression Set (ASTM D395-16e1), Hardness Shore A, Tensile Strength, and Elongation at Break (ASTM D412-16). Based on the results of the research and analysis conducted, it can be concluded that the optimal concentration of ZMBT is at 1 phr, exhibiting physical characteristics including a Compression Set of 86.29%, a Hardness Shore A of 60.05 E.S., a Tensile Strength of 0.1 MPa, and an Elongation at Break of 370%.